Light source integrated OPFET (LSI-OPFET): A new integrated device for optically controlled varying gain amplifier - Jit S.; Pal B.B. (My University, 2025)
A new optoelectronic integrated device consisting of an n-GaAs optical field-effect transistor (OPFET) and a p- AlGaAs/p-GaAs/n+-AlGaAs surface emitting double heterostructure light emitting diode (DH-LED) which are developed monolithically on a p+-GaAs subtrate and separated by a thin semi-insulating GaAs layer, is proposed in this paper. We call this device as Light Source Integrated-OPFET (LSI-OPFET). The proposed device structure is such that the optical radiation generated by the LED is fed into the OPFET as back illumination. The back radiation is used as the control signal to the OPFET which changes the transconductance of the OPFET. The intensity level of the back illumination to the OPFET can be controlled by changing the bias current of the LED. In this paper, analytical results have been presented for the I-V characteristics and transconductance of the OPFET as a function of the LED current. It has been shown that by changing the level of the back illumination to the OPFET, i.e. by changing the LED current, one can vary both the characteristics and transconductance, which makes the LSI-OPFET as the potential device for the optically controlled varying gain amplifier.